Gastric antral vascular ectasia in children, rare presentation. Issue 11 (30th November 2020) - Pizzuto, Matthew; Ellul, Sarah; Shoukry, Mohamed
Abstract : A 14-year-old boy, a known case of perinatal hypoxic cerebral palsy, presented to paediatric emergency with acute melaena and blood staining around feeding gastrostomy site. Physical examination revealed pallor, but no signs of distress with an unremarkable abdominal examination. Routine blood tests revealed normochromic. Abdominal ultrasound scan and Meckel's scan were unremarkable. The patient underwent examination under anaesthesia of the perianal area and joint upper and lower gastrointestinal endoscopy. Streak-like gastritis with no signs of active bleeding lesions were noted and patchy areas of colitis involving the descending and sigmoid colon and the rectum. All clinical findings and evidence-based diagnosis matched gastric antral vascular ectasia. He was successfully managed conservatively with elemental hydrolysed feeding formula.